Ab initio results for the plasmon dispersion and damping of the warm dense electron gas. Issue 10 (21st September 2020) - Hamann, Paul; Vorberger, Jan; Dornheim, Tobias; Moldabekov, Zhandos A.; Bonitz, Michael
Abstract: Warm dense matter (WDM) is an exotic state on the border between condensed matter and dense plasmas. Important occurrences of WDM include dense astrophysical objects, matter in the core of our Earth, and matter produced in strong compression experiments. As of late, x‐ray Thomson scattering has become an advanced tool to diagnose WDM. The interpretation of the data requires model input for the dynamic structure factor S ( q,   ω ) and the plasmon dispersion ω ( q ). Recently, the first ab initio results for S ( q,   ω ) of the homogeneous warm dense electron gas were obtained from path integral Monte Carlo simulations (Dornheim et al., Phys. Rev. Lett., 121, 255001, 2018). Here, we analyse the effects of correlations and finite temperature on the dynamic dielectric function and the plasmon dispersion. Our results for the plasmon dispersion and damping differ significantly from the random‐phase approximation and from earlier models of the correlated electron gas. Moreover, we show when commonly used weak damping approximations break down and how the method of complex zeroes of the dielectric function can solve this problem for WDM conditions.